MULTIMODAL CONTRASTIVE ANALYSIS OF PEPSODENT EXPERT PROTECTION TV COMMERCIALS IN 2013 - ROSYID ANWAR, 121211232003 (2016)
Pepsodent Expert Protection commercials use multimodality as a way of creating meaning by using various modes. This study aims to analyze the use of multimodal elements in commercials with informative and persuasive nature. The linguistic mode is analyzed by using Systemic Functional Linguistics proposed by Halliday, while the para-linguistic mode is analyzed by using grammar of visual design proposed by Kress and van Leeuwen. The data is in form of TV commercials published on 5 February 2013 and 29 October 2013 by Pepsodent official account on Youtube. Qualitative method is used to give descriptive analysis and in-depth understanding. The commercials use ideational metafunction to bring up humans’ experience in the real world into verbal message that can be communicated. From the aspect of visual imagery, interactive participant is considered important and depicted more saliently. In terms of interpersonal metafunction, high polarity declarative and interrogative are combined with indirect gaze and low camera angle in the first commercial that has informative nature. Median polarity declarative, interrogative, and imperative are combined with indirect and direct gaze, close-up shot, eye level shot, long shot, and low angle in the second commercial that has persuasive nature. Textual metafunction is used to connect ideas relevantly and logically in verbal mode. In terms of visual imagery, textual metafunction used to combine elements in an image. The combination of linguistic and para-linguistic modes is used in the commercials to form the overall message. The first commercial has an informative nature. The second commercial has more persuasive nature.